Peaceful-Oriented Communication for Reduction of Hate Speech Abused by Thai Youth in the 21st Century - Eakwilai, Wasaya; Soommat, Kusuma; Phansawang, Jiraporn; Phongsuwan, Risorn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of the research article were 1) to analyze the language tactics showing the violence of Facebook users in their comments 2) to analyze the social factors associated with the language tactics showing the violence of Facebook users in their comments and 3) to create innovations by the use of peaceful communication with the principles of Principles of Proverbs, Principles of virtues conducive to growth, and Four Rddhippada to reduce the violence of language usage of Thai in the 21st century. It is a quantitative research. The research instruments were questionnaires. The statistics used in the research were percentage, mean and standard deviation. The results were as follows : 1. Language strategies contains words for verbal abuse in the news before the election, the news after the election, and social disparity news were classified into 5 groups as follows : 1) words for verbal abuse on political group, 2) words for verbal abuse on occupation and specialized interest groups, 3) words for verbal abuse on non-human group, 4) words for verbal abuse on religion, 5) words for verbal abuse on regional ethnicity 2. Social factors associated with language strategies were: 1) the need for an identity on social media, 2) the need for recognition or prominence on social media, 3) Innovations that use peaceful communication to reduce the violence of language usage of Thai the 21st century using the 7-step rainbow model: 1) Growth concept, 2) Critical thinking skills, 3) Communication skills in conflict situations, 4) Social skills, 5) Four Rddhippada, 6) Principles of virtues conducive to growth, 7) Principles of Proverbs.